Does Downside Risk Matter more in Asset Pricing? Evidence from Indonesia - Iman Lubis; Nailin Nikmatul Maulidiyah (YPPP AL-AMSI, 2022)
This study examines downside risk matters in asset pricing, particularly evidence from Indonesia. Using ten reference indexes for passive instruments and 674 companies listed on the Indonesia Stock Exchange between 2020-2021. The four measurements are the traditional families (beta and standard deviation/risk) and downside risk families (semi-deviation and downside beta). For those, we divide 674 stocks into quintiles (5 groups). Every quintile is investigated by four measurements using Fama-Macbeth regression. semi-deviation in those close to standard deviation. Standard deviation affects semi-deviation portfolios in quintiles 1 and 2 and portfolios sorted beta and downside beta in quintile 2. Beta does not affect all portfolios. Eighth, semi-deviation affects portfolios sorted semi-deviation in quintiles 1,2,3,and 5. Downside beta does not affect all portfolios.